M1AP interacts with the mammalian ZZS complex and promotes male meiotic recombination. (28th November 2022) - Li, Yang; Wu, Yufan; Khan, Ihsan; Zhou, Jianteng; Lu, Yue; Ye, Jingwei; Liu, Junyan; Xie, Xuefeng; Hu, Congyuan; Jiang, Hanwei; Fan, Suixing; Zhang, Huan; et al.
Abstract: Following meiotic recombination, each pair of homologous chromosomes acquires at least one crossover, which ensures accurate chromosome segregation and allows reciprocal exchange of genetic information. Recombination failure often leads to meiotic arrest, impairing fertility, but the molecular basis of recombination remains elusive. Here, we report a homozygous M1AP splicing mutation (c.1074 + 2T > C) in patients with severe oligozoospermia owing to meiotic metaphase I arrest. The mutation abolishes M1AP foci on the chromosome axes, resulting in decreased recombination intermediates and crossovers in male mouse models. M1AP interacts with the mammalian ZZS (an acronym for yeast proteins Zip2‐Zip4‐Spo16) complex components, SHOC1, TEX11, and SPO16. M1AP localizes to chromosomal axes in a SPO16‐dependent manner and colocalizes with TEX11. Ablation of M1AP does not alter SHOC1 localization but reduces the recruitment of TEX11 to recombination intermediates. M1AP shows cytoplasmic localization in fetal oocytes and is dispensable for fertility and crossover formation in female mice. Our study provides the first evidence that M1AP acts as a copartner of the ZZS complex to promote crossover formation and meiotic progression in males. Synopsis: M1AP acts as a male‐specific copartner of the ZZS complex to stabilize recombination intermediates and promote crossover formation. Disruption of M1AP causes meiotic metaphase I arrest and impairs male fertility in humans and mice. M1AP deficiency reduces crossover formation and causes meiosis arrest at the metaphase I stage in males but not females. M1AP colocalizes with TEX11 in a SPO16‐dependent manner in spermatocytes but shows cytoplasmic localization in fetal oocytes. M1AP interacts with the ZZS complex and promotes the recruitment of TEX11 at the recombination intermediates in spermatocytes. Abstract : M1AP acts as a male‐specific copartner of the ZZS complex to stabilize recombination intermediates and promote crossover formation. Disruption of M1AP causes meiotic metaphase I arrest and impairs male fertility in humans and mice.